2023
DOI: 10.1186/s12889-023-16114-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of e-trainings in occupational safety and health: a literature review

Abstract: Background Implementing workplace preventive interventions reduces occupational accidents and injuries, as well as the negative consequences of those accidents and injuries. Online occupational safety and health training is one of the most effective preventive interventions. This study aims to present current knowledge on e-training interventions, make recommendations on the flexibility, accessibility, and cost-effectiveness of online training, and identify research gaps and obstacles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 223 publications
0
2
0
Order By: Relevance
“…Therefore, OSH training should focus on making workers aware of the need to carry out their work in such a way that their health is maintained at the highest level. This is also confirmed in the work of Barati Jozan et al [94], who show that effectively improving workers' knowledge and skills ultimately leads to fewer accidents and injuries in the workplace.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, OSH training should focus on making workers aware of the need to carry out their work in such a way that their health is maintained at the highest level. This is also confirmed in the work of Barati Jozan et al [94], who show that effectively improving workers' knowledge and skills ultimately leads to fewer accidents and injuries in the workplace.…”
Section: Discussionmentioning
confidence: 56%
“…Another study in India also revealed that educational workshops improved HCWs’ knowledge about occupational hazards [ 26 ]. A literature review study also highlighted the positive impacts of e-training programs on employees’ knowledge and behavior regarding occupational health and safety and reducing workplace injuries [ 27 ]. These findings are consistent with the present study regarding the impact of educational intervention on individuals’ protective behaviors against occupational hazards, also it should be denoted that some parts of the educational intervention in the present study were delivered virtually on mobile platforms.…”
Section: Discussionmentioning
confidence: 99%